Simple Sequencing Problems with Interdependent Costs - Manipushpak Mitra; Roland Hain (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
In this paper we analyze sequencing situations under incomplete information where agents have interdependent costs. We first argue why Vickrey-Clarke-Groves (or VCG) mechanism fails to implement a simple sequencing problem in dominant strategies. Given this impossibility, we try to implement simple sequencing problems in ex-post equilibrium. We show that a simple sequencing problem is implementable if and only if the mechanism is a `generalized VCG mechanism'. We then show that for implementable n agent simple sequencing problems, with polynomial cost function of order (n-2) or less, one can achieve first best implementability. Moreover, for the class of simple sequencing problems with ``sufficiently well behaved'' cost function, this is the only class of first best implementable simple sequencing problems.
Keywords: C44; C72; C78; D82; 330; Simple Sequencing Problems; Ex-post Equilibrium; First Best Implementability